Analyzing the indicators of choosing the appropriate teaching method for Education the principles of accounting (1) using the Meta-synthesis method - Hossein Esmailkhani; Mahmoud Moeinaldin; Forough Heirany (مدیریت و چشم انداز آموزش)
The aim of the current research is to analyze the indicators of choosing the appropriate teaching method for teaching the principles of accounting (1) in a meta-composite method. According to its purpose, the research method is applicable, and in terms of execution method, it is qualitative, and in a meta-composite method. The statistical population of this research includes 9 experts and professors in the field of accounting education. By analyzing previous studies and extracting the effective dimensions, the MAXQDA 2018 software was used to code the categories, which were categorized into 8 core categories and 39 open codes, then using the fuzzy screening method and with the participation of experts and professors, the importance of each category was determined. The results showed that out of the 39 categories extracted in the meta-combination stage, 21 categories are very important from the experts' point of view. Also, the prioritization of the categories showed that the indicators of teaching time and knowledge or scientific qualification of the professor are criteria with the highest level of importance for choosing a suitable teaching method for teaching accounting principles (1). The findings show that in order to choose a suitable teaching method for teaching accounting principles (1), professors and lecturers in the field of accounting education should pay attention to the indicators that affect the selection of the appropriate teaching method and take into account the important role of the mentioned indicators; and improve students' learning and performance by choosing appropriate teaching methods,. Extended abstract Introduction Higher education is crucial for knowledge-based economies and globalization. Countries that neglected higher education in the past are paying a heavy price in terms of the decline of the intellectual community. According to a World Bank report, economies that pay less attention to higher education will never benefit from a knowledge-based economy (Fatima, 2018). Otunga & Nyandusi (2011) believe that teachers should use teaching methods that allow learners to participate in learning. They also argue that learning is best when learners are engaged, and that teachers should do everything possible to make teaching and learning interactive. In other words, teachers should use the appropriate educational and learning content and allow students to interact with the educational and learning content, so that effective learning is achieved; therefore, the teacher should be able to use appropriate teaching methods according to the conditions. However, teaching science is a difficult task, especially in classrooms that are not adequately equipped, and the teacher has limited teaching resources (Twumasi, 2020). Commission for Change in Accounting Education (1992) emphasized the importance of the introductory accounting course as the cornerstone of success in subsequent courses. In part of the objectives of the course, the commission refers to the understanding of the basic concepts of accounting and the elements of financial statements and recommends that the introductory accounting courses be taught by the best lecturers of the faculties, and that students should be active in the learning process and not just passive recipients of information. Such an emphasis on the importance of accounting introductory courses and making it attractive can also be seen in the final report of the Future Perspectives Commission (Spiceland et al, 2015). Therefore, the researcher is trying to answer the main question: what are the indicators of choosing the appropriate teaching method for the teaching of accounting principles (1) with the meta-composition method. Theoretical Framework Teaching Teaching is the art of liberating the learner's inherent potential and includes three elements: learner, content, and teacher. In teaching and learning, these elements interact with each other and methods bring them together at any time of teaching and learning. The ability to do this requires choosing the most appropriate strategy that ensures optimal absorption of the educational content by the provider. However, two main approaches; teacher-centered and student-centered teaching depends on classroom interaction and the choice of different methods by which students can learn science (Duruji et al, 2014). As a result of the era of globalization and postmodernism, the efforts of higher education institutions to maintain resource centers in order to make it possible to maintain educational resources to meet the accreditation standard of educational programs should be mentioned. Teaching aids enable the teacher to do his job well and help learners to learn selectively (Eliasu et al, 2016). Again, other studies show that the quality of resources, physical facilities and human resources affect the quality of teaching and learning. This shows that identifying a suitable teaching method is essential for quality education. The quality of education is mostly measured by the performance of learners or students. This shows that in order to ensure a quality education, it is almost inevitable to emphasize the use of appropriate teaching methods. Also, since the educational system is more committed to entrepreneurship and skill-based learning, it becomes necessary to use appropriate teaching methods that enable students to adopt practical skills (Memory Queensoap, 2020). Mohammadpor (2020) conducted a research entitled "New accounting teaching methods" with the aim of introducing new teaching methods; the results of his research show that accounting education should first teach accounting knowledge and theory, and then teach technical skills, and this requires the creation of extensive relationships between education officials, entrepreneurs and learners, as well as creating a competitive environment that enables accounting graduates to innovate and transfer acquired knowledge and skills. Zeinali et al, (2020) conducted a research titled "The role of new educational methods in the interactive relationship between teachers and students" among 40 experts who had at least 5 years of experience in teaching students. The results of their research show that traditional teaching methods do not play a role in the interactive communication of teachers and students, but modern teaching methods play a role in the interactive communication of teachers and students, and the obstacles of modern teaching methods play a role in the interactive communication of teachers and students. Research methodology According to its purpose, the research method is applicable, and in terms of execution method, it is qualitative, and in a meta-composite method. The statistical population of this research includes 9 experts and professors in the field of accounting education. Research findings By analyzing previous studies and extracting the effective dimensions from the MAXQDA 2018 software, it was used to code the categories, and the categories were categorized into 8 core categories and 39 open codes, then using the fuzzy screening method and with the participation of experts and professors, the importance of each category was determined. The results showed that out of the 39 categories extracted in the meta-composition stage, 21 categories are very important from the experts' point of view. Also, the prioritization of the categories showed that the indicators of teaching time and knowledge or scientific qualification of the professor are criteria with the highest level of importance for choosing a suitable teaching method for teaching accounting principles (1). The findings show that in order to choose a suitable teaching method for teaching accounting principles (1), professors and lecturers in the field of accounting education should pay attention to the indicators that affect the selection of the appropriate teaching method and take into account the important role of the mentioned indicators; and improve students' learning and performance by choosing appropriate teaching methods. Conclusion The current research was conducted with the aim of analyzing the indicators of choosing the appropriate teaching method for teaching accounting principles (1) using a meta-composite method. The results of this research are in accordance with the research results of Mohammadpor (2020), Zeinali et al, (2020), Piri Sagharloo et al, (2021), Rahmanian koushkaki et al, (2021), Rajeevan (2019), sarea et al, (2021), Nghiem-Phu & Nguyen (2021), and Amesi et al, (2023). In general, the results show that according to the analysis of the identified dimensions and indicators to choose a suitable teaching method for teaching accounting principles (1), the selection of a suitable teaching method should be done according to the identified indicators and the selected method should have the highest benefit from the identified indicators in the relevant educational situation. According to research of Cheruiyot (2019), experience is not an attribute that can be acquired immediately. Proper training is a basic requirement and experience will be gained over time. Experience is thought to be the "best teacher" in teaching; therefore, in examining the effectiveness of teaching, the variable of teaching experience should be revealed. In addition, experience affects the teaching style, so that one gradually becomes more and more self-confident. When comparing experienced and inexperienced classroom teachers, there are differences in instructional and other aspects of classroom work (Cheruiyot, 2019). According to the results of the present research, it is suggested that the following research should be considered in the field of accounting education: - Providing a comprehensive and appropriate model for teaching accounting courses - Identifying appropriate and practical teaching methods for teaching each of the accounting courses with an applicable approach. It is emphasized that the authors are required to declare any conflict of financial or organizational interests and the measures taken to control and manage it, in order to maintain transparency and reliability in scientific research. In the end, gratitude is expressed to all the people and organizations that played a role in conducting this research and preparing the article.